2004
DOI: 10.1002/ijc.20216
|View full text |Cite
|
Sign up to set email alerts
|

Novel camptothecin analogues that circumvent ABCG2‐associated drug resistance in human tumor cells

Abstract: Key words: SN-38; CPT analogue; ABCG2; SAR; DNA topoisomerase I inhibitorCamptothecin (CPT) is an antitumor alkaloid that was originally isolated from Camptotheca acuminata, a tree native to southern China. 1 CPT has been demonstrated to inhibit mammalian DNA topoisomerase I (Topo I), the nuclear enzyme that changes the topologic state of duplex DNA by single-strand breakage and resealing. Stabilization of the covalent Topo I-DNA complex (so-called cleavable complex) by CPT is a critical step in its antitumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…Moreover, we found that the presence of a corresponding R1 position hydroxyl is necessary to facilitate ABCG2-mediated drug resistance also toward the distinct pharmacological group of TAs. In accord, a recent study on the nature of ABCG2 interaction with camptothecin analogs has revealed a similar dependence on the presence of hydroxyl or amine groups on the outer ring of their common camptothecin structure, possibly facilitating hydrogen bond formation, essential for substrate recognition and efflux via ABCG2; these camptothecin positions seem to be analogous to the present R1, R2, or R3 positions of IAs (Yoshikawa et al, 2004). Several subsequent publications on ABCG2-dependent resistance to novel camptothecin analogs have also obeyed this general hydrogen bond rule (Rajendra et al, 2003;Bates et al, 2004;Takagi et al, 2007).…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, we found that the presence of a corresponding R1 position hydroxyl is necessary to facilitate ABCG2-mediated drug resistance also toward the distinct pharmacological group of TAs. In accord, a recent study on the nature of ABCG2 interaction with camptothecin analogs has revealed a similar dependence on the presence of hydroxyl or amine groups on the outer ring of their common camptothecin structure, possibly facilitating hydrogen bond formation, essential for substrate recognition and efflux via ABCG2; these camptothecin positions seem to be analogous to the present R1, R2, or R3 positions of IAs (Yoshikawa et al, 2004). Several subsequent publications on ABCG2-dependent resistance to novel camptothecin analogs have also obeyed this general hydrogen bond rule (Rajendra et al, 2003;Bates et al, 2004;Takagi et al, 2007).…”
Section: Discussionmentioning
confidence: 70%
“…Although the number of known BCRP substrates is now over 200, not much work has been done to analyze structure-activity relationship (SAR). The only SAR study was for camptothecin analogs, and the authors found that BCRP preferentially transports the camptothecin analogs with high polarity at carbon positions 10 and 11 over those with low polarity (41). We have recently developed a predictive model for BCRP substrates using a support vector machine (SVM) method based on 263 known BCRP substrates and non-substrates (42).…”
Section: Bcrp Substratesmentioning
confidence: 99%
“…The high-performance liquid chromatography retention time of the compounds, as measured using a reverse phase column, correlated inversely with the drug resistance ratio where compounds with a short retention time had higher ratios and vice versa. The SAR showed that SN-355, SN-392, and SN-398 have similar substituents on the 10 and 11 positions making these compounds susceptible to transport by ABCG2 like SN-38 (37). Based on the SAR, it was speculated that the remaining SN-38 analogues would be able to circumvent efflux by ABCG2.…”
Section: Sar and Qsar Of Abcg2 Substratesmentioning
confidence: 99%